Eine Klein(e) Kammer - Kent Kleinman; Leslie Van Duzer (Oz, 1998)
This is the story of a little chamber—the so-called "Klein Room"—in an underestimated work—Haus Lange—by a major architect, Mies van der Rohe. The story concerns a moment of resignation embedded within a larger context of compromise.